X-Ray Transients in the SRG/eROSITA All-Sky Survey. Issue Volume 14:Issue S339(2018) (November 2017) - Rau, A.
Abstract: eROSITA (the extended ROentgen Survey with an Imaging Telescope Array) onboard the Spectrum Roentgen Gamma mission will perform a deep all-sky X-ray survey. During the first four years of operation the satellite will scan the entire sky every once every half year, visiting any position between 8 and 500 times. The eROSITA scanning strategy will test a wide range of times-scales, from seconds to years, and thus provide a powerful window into the X-ray transient and variable sky. This contribution summarised the key science opportunities for time-domain studies with eROSITA, and presented strategies for finding transients in the all-sky survey data.